Implementasi Pembiayaan Musyarakah Mutanaqisah di Perbankan Syariah Indonesia - Hadiat, Hadiat; Mukhlas, Oyo Sunaryo; Rusyana, Ayi Yunus (PT. Alahyan Publisher Sukabumi, 2024)
This study aims to investigate the implementation of musyarakah mutanaqishah financing in sharia banking in Indonesia, specifically by considering three issues related to contract implementation: sharia issues, legal issues and operational issues. This research was conducted through a combination of descriptive qualitative methods and inductive analysis. The results of the analysis are based on Law of the Republic of Indonesia Number 21 of 2008 concerning Sharia Banking, DSN-MUI Fatwa Number 73/2008 concerning Musyarakah Mutanaqishah, and AAOIFI sharia standards. From a legal and operational analysis perspective based on BI regulations regarding banking laws, it is indicated that there is a discrepancy between the basic regulations and implementation in the field. Regarding operations, there is a delegation of all payment obligations for costs that arise in deviation from AAOIFI standards and DSN fatwas and there are no specific accounting standards related to MMQ.